Togo : Sixth Review under the Extended Credit Facility Arrangement and Request for Augmentation of Access-Press Release; Staff Report; and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Togo's Sixth Review Under the Extended Credit Facility (ECF) Arrangement and Request for Augmentation for Access. Togo's performance under the ECF-supported program has been broadly satisfactory. While the economic recovery was firming up, it has recently been hindered by the coronavirus disease 2019 pandemic. The macroeconomic outlook is subject to a high degree of uncertainty. Structural reforms are progressing on revenue administration and public financial management. Progress has been made on collection of tax arrears, online submission of customs declarations, and steps toward program-based budgeting. It will be important to implement recommendations from a recent Tax Administration Diagnostic Assessment Tool, address remaining deficiencies in essential customs functions, and bolster voluntary compliance to ensure strong permanent revenue. Togo is amongst the best performers in the improvement of the business environment in recent years. It will be important to pursue such reforms, including strengthening governance, and to implement the measures outlined in the National Development Plan to support strong and inclusive growth. Completing the delayed reforms of the two state-owned banks is paramount to safeguarding financial stability and preventing risks to the state budget.